2014
DOI: 10.2478/s11535-014-0300-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro organogenesis secondary metabolite production and heavy metal analysis in Swertia chirayita

Abstract: An efficient protocol of plant regeneration through direct and indirect organogenesis in Swertia chirayita was developed. Explants cultured on Murashige and Skoog medium supplemented with 2,4-D (0.5 mg L−1) with combination of Kinetin (0.5 mg L−1) showed the highest frequency (84%) of callusing and 1.0mg L−1 6-benzyladenine (BA) in combination with (100 mg L−1) Adenine sulphate (Ads) + (0.1 mg L−1) Indole acetic acid (IAA) was excellent for maximum adventitious shoot (12.69 ± 1.30) formation in four week of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…He also reported higher amounts of xanthone compounds in in vitro raised plantlets in comparison to naturally growing plantlets. Similarly, higher concentration of mangiferin and swertiamarin in in vitro compared to wild plant extracts has been recently reported by Kumar et al (2014). Initially, full scan LC/ESI-MS spectra of in vivo and in vitro S. chirayita methanolic extracts was acquired in positive ion mode utilizing the LC gradient condition as described earlier with a mobile phase consisting of acetonitrile and 5 mM ammonium acetate pH4.2.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…He also reported higher amounts of xanthone compounds in in vitro raised plantlets in comparison to naturally growing plantlets. Similarly, higher concentration of mangiferin and swertiamarin in in vitro compared to wild plant extracts has been recently reported by Kumar et al (2014). Initially, full scan LC/ESI-MS spectra of in vivo and in vitro S. chirayita methanolic extracts was acquired in positive ion mode utilizing the LC gradient condition as described earlier with a mobile phase consisting of acetonitrile and 5 mM ammonium acetate pH4.2.…”
Section: Resultsmentioning
confidence: 95%
“…Following the procedure described by Kumar et al (2014) leaf explants excised from young plants were decontaminated in 0.2% Bavastin solution followed by (5-6drops/100 mL) Tween 20 (20 min) and 0.1% mercuric chloride (8 min). The leaf explants were rinsed three times in sterile distilled water, cut into approximately 1 cm Indole-3-acetic acid (IAA), and 0.8 % agar, pH 5.8.…”
Section: Plant Materialsmentioning
confidence: 99%
“…In addition, synthesis and gene expression levels of the secondary metabolites can be greatly influenced by the nutrient contents and plant hormones employed during the in vitro culture [ 35 ]. Likewise, the secondary metabolites production in in vitro plantlets was higher in Swertia chirayita than in vivo plantlets [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that the development of efficient micropropagation protocols, can guarantee an adequate supply of S. chirayita plants (devoid of environmental-imposed constraints) with subsequent reduction in uncontrolled harvesting pressure on wild populations. Several studies reported on micropropagation, somatic embryogenesis and acclimatization procedures with the capacity to produce many uniform S. chirayita clones throughout the year (Kumar and Chandra, 2013 , 2014 ; Kumar et al, 2014 ). As shown in Table 5 , micropropagation protocols have successfully been established for S. chirayita using different explants.…”
Section: Swertia Chirayita Conservationmentioning
confidence: 99%
“…Due to its excessive over-exploitation from the natural habitat, narrow geographic occurrence (Bhat et al, 2013 ) and unresolved inherent problems of seed viability and seed germination (Badola and Pal, 2002 ; Joshi and Dhawan, 2005 ), alternative approaches for propagation and conservation are urgently required to avoid the possible extinction of this important species. Consequently, S. chirayita has been receiving increasing attention from a wide range of researchers as evident from the number of publications appearing in the literature (Chen et al, 2011 ; Nagalekshmi et al, 2011 ; Ghosh et al, 2012 ; Kumar and Chandra, 2013 , 2014 , 2015 ; Fan et al, 2014 ; Kumar et al, 2014 ; Sharma et al, 2014 , 2015 ; Padhan et al, 2015 ; Zhou et al, 2015 ). However, a comprehensive review detailing the documented ethnomedicinal uses, pharmacological properties and safety evaluation carried out on S. chirayita and identifying the existing knowledge gap is lacking.…”
Section: Introductionmentioning
confidence: 99%